Diagnosis dan Tatalaksana Perdarahan Saluran Cerna Atas Pada Pengguna NSAID Jangka Panjang : Laporan Kasus - Haitsam, Muhamad Haitsam; Wardhani, Shinta; Yudha, Fakhmi (Jurnal Klinik dan Riset Kesehatan, 2024)
Upper gastrointestinal bleeding is one of the most frequently encountered emergency cases. For most general practitioners, diagnosing and providing initial management is a challenge in itself. Upper gastrointestinal bleeding is divided into variceal and non-variceal bleeding. Clinical symptoms that can be found include hematemesis or melena. Patients with melena tend to have lower hemoglobin (Hb) levels than hematemesis because clinical manifestations appear more slowly. Drug Induced NSAIDs are also one of the etiologies that can cause upper gastrointestinal bleeding. Endoscopy is the gold standard for diagnosis, but not all health facilities are able to perform it. This case reported a 66-years-old male patient came to the emergency room with complaints of blackish stools with a soft, sticky consistency for 6 days, accompanied by weakness, dizziness, nausea in the stomach and disruption of daily activities. The patient has a history of taking over-the-counter NSAIDs long term to relieve his knee pain. On physical examination, hepatomegaly and splenomegaly were not found and the patient’s hemodynamics is stable. On laboratory examination, Hb was found to be 3.4 g/dl. It was suspected that there was upper gastrointestinal bleeding, then received therapy in the form of PPI injections, antiemetic injections and planned PRC transfusion.